Aerobic Exercise as an Essential Component of Non-Pharmacological Management for Metabolic Syndrome - A Review - Swojnóg, Marzena; Barczewska, Magdalena; Bieszczad, Dominika; Reizer, Barbara; Botto, Zofia; Felisiak, Patrycja; Kowalczyk, Dominika; Śliwa, Zofia; Ślazyk, Dominik Andrzej; Krystek, Klaudia (Quality in Sport, 2026)
Background. Metabolic Syndrome (MetS) is a prevalent cluster of conditions that significantly increases the risk of cardiovascular disease and type 2 diabetes mellitus. Lifestyle modification is universally recognized as the primary therapeutic strategy, with aerobic exercise playing a crucial role in improving metabolic health and reducing mortality risks in affected populations. Aim. This review synthesizes current evidence on the efficacy and mechanisms of aerobic exercise as a fundamental non-pharmacological strategy for managing Metabolic Syndrome (MetS). Material and methods. A search of major databases (2015–2025) was performed, focusing on systematic reviews and RCTs. Keywords included "Metabolic Syndrome," "aerobic exercise," "insulin resistance," "dyslipidemia," and "exercise prescription." Results. Regular aerobic exercise improves cardiometabolic risk factors independently of significant weight loss. It enhances insulin sensitivity via GLUT4 translocation, optimizes the lipid profile (reducing triglycerides, increasing HDL), and reduces visceral adiposity and inflammation. Additionally, High-Intensity Interval Training (HIIT) is highlighted as a potent strategy, often offering superior efficacy to moderate-intensity continuous training (MICT). Conclusions. Aerobic exercise is an essential component of MetS management. Professionals should prioritize individualized prescriptions, incorporating both MICT and HIIT, to effectively mitigate cardiometabolic risk and improve patient health.